The Death Rite in New Republic Nepal: Should It Be Shortened? - Rijal, Shiva Ram (SCHOLARS: Journal of Arts & Humanities, 2019)
I introduce an on-going debate on whether and how should rituals be tamed in the contemporary Hindu society of Nepal. In this paper, I point out intellectuals who espouse secular thoughts hesitate to talk about rituals in public. On the other hand, there are also many who believe these rituals as their forte. Out of this trajectory of thoughts, I develop an argument that there is a lack of force that could promote interpretative understanding of rituals in Nepal. Based on a line of thoughts propounded by Roy A. Rappaport, Catherine Bell, and Hannah Arendt, I maintain that rituals need to be taken as part and parcel of ritual-making zeal of humankind. With a brief introduction about the historicity of ritualization in Nepal, I highlight the adoptable characteristics of rituals in the Kathmandu Valley and the role the people of the valley have started to point out a possibility of bringing reformation in death rituals.